2016
DOI: 10.1002/mrm.26255
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tissue T1on perfusion measurement with arterial spin labeling

Abstract: A low dose of Mn reduces the tissue T without modifying CBF. Heterogeneous T impacts the ASL estimate of CBF in a region-dependent way. In animals, and when T modifications exceed the accuracy with which the tissue T can be determined, an estimate of tissue T should be obtained when quantifying CBF with an ASL technique. Magn Reson Med 77:1656-1664, 2017. © 2016 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Measurement of venous oxygenation is a critical step toward noninvasive assessment of brain metabolism and energy consumption. To estimate CMRO 2 , one can combine TRUST MRI with additional measures of arterial oxygenation and cerebral blood flow (CBF), which can be obtained with phase‐contrast MRI or arterial‐spin‐labeling . Previous studies in humans have demonstrated the clinical utility of these techniques in several neurologic diseases such Alzheimer's disease and multiple sclerosis .…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of venous oxygenation is a critical step toward noninvasive assessment of brain metabolism and energy consumption. To estimate CMRO 2 , one can combine TRUST MRI with additional measures of arterial oxygenation and cerebral blood flow (CBF), which can be obtained with phase‐contrast MRI or arterial‐spin‐labeling . Previous studies in humans have demonstrated the clinical utility of these techniques in several neurologic diseases such Alzheimer's disease and multiple sclerosis .…”
Section: Discussionmentioning
confidence: 99%
“…The following sequences were used in this study, but not all for each animal (see “Experimental Protocols” subsection for more details): Anatomical T 2 ‐weighted (T 2w ) images were obtained through a spin‐echo sequence (TR/TE = 3346/33 ms, resolution = 0.137 × 0.137 × 0.8 mm 3 , number of averages (NA) = 2, acquisition time (T acq ) = 3 min 34 s). A T 1 map was acquired for cerebral blood flow (CBF) quantification using a nonselective inversion recovery sequence (TR/TE = 10000/19 ms, 18 inversion times (TIs) between 30 and 10000 ms, T acq = 4 min). Other EPI parameters were identical to the aforementioned ones. Label‐phase optimization prescan (T acq = 100 s).…”
Section: Methodsmentioning
confidence: 99%
“…To calculate quantitative CBF maps, we assumed a single compartment and used the standard kinetic model developed by Buxton et al . Assuming that the arterial transit time is equal to the postlabeling delay, and that M0b, the magnetization of arterial blood at thermal equilibrium, may be approximated by M0t/λ, where M0t is the magnetization of tissue at thermal equilibrium and λ the blood‐brain partition coefficient of water (0.9 mL/g) , we used the following equation pixel‐by‐pixel to quantify CBF (mL/100 g/min) : CBF=6000λΔMexp(ω/T1b)2 IE T1tM0t(1exp(τ/T1t)), where ΔM is the signal difference between control and label acquisitions averaged over repetitions; T1t is the apparent T 1 of tissue from the T 1 map; T1b is the longitudinal relaxation time of blood (2430 ms at 9.4 T) ; and M0t is the control image intensity of the ASL experiment multiplied by [1exp(TR/T1t)]1 to correct for incomplete T 1 relaxation during the 4‐s TR.…”
Section: Methodsmentioning
confidence: 99%
“…As a result of the above issues, a wide range of CBF measurements in rodents have been reported, often spanning ranges that are neither physiologically realistic (e.g. >300 mL/100 g/min 610 ), nor in agreement with gold-standard autoradiography measures of perfusion. 11 Thus, there is a need to improve the application of ASL MRI in rodents and to achieve a similar standardization to that now implemented clinically.…”
Section: Introductionmentioning
confidence: 99%